2019
DOI: 10.1177/0002764219831735
|View full text |Cite
|
Sign up to set email alerts
|

Political Generations and the Italian Environmental Movement(s): Innovative Youth Activism and the Permanence of Collective Actors

Abstract: During recent years, Italian social movements have experienced a period of crisis, in part due to diffuse antipolitical feelings and latent social conflict. However, environmental issues and especially territorial mobilizations remain relevant, due to the appearance of new contentious actors and to the permanence of long-standing organizations and important local grassroots campaigns. Based on 19 semistructured interviews with activists belonging to informal groups and formal associations, this article discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 68 publications
0
14
1
3
Order By: Relevance
“…Contrary to current studies on Italian environmental activism (Bertuzzi 2018), we found that FFF-activists believe climate activism to be their own fight. They accentuate the understanding of climate change as a generational issue, usually described as particularly affecting teenagers and young adults, as its consequences will be more severe in their future.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to current studies on Italian environmental activism (Bertuzzi 2018), we found that FFF-activists believe climate activism to be their own fight. They accentuate the understanding of climate change as a generational issue, usually described as particularly affecting teenagers and young adults, as its consequences will be more severe in their future.…”
Section: Discussioncontrasting
confidence: 99%
“…A growing number of studies has also addressed youth environmental activism (Gallay et al, 2016;O'Brien et al, 2018). While youth-driven discourses coalesce around environmental justice, scholars have commented on the intersectional (Terriquez et al, 2018) as well as anti-capitalist (Bertuzzi, 2019) collective action frames within contemporary environmental youth movements. In the spirit of cross-issue activism and transnationalization, the discourses of youth environmental activism also resonate with other social justice collectives, including anti-racist (Bullard, 1993), LGBTQ or labor rights (Almeida, 2019) agendas.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The analysis is based on 19 semi-structured interviews with formal or charismatic leaders of some relevant groups and associations in Italy. These range from traditional ENGOs (national ones or Italian branches of international ones) to LULU movements (della Porta et al, 2019;della Porta & Piazza, 2008), networks of independent alternative farmers and political ecology groups (Bertuzzi, 2019a). As anticipated, I argue that this classic contraposition between reformist and radical approaches translates into an even broader distinction between green democracy and ecological democracy.…”
Section: The Researchmentioning
confidence: 83%
“…At the same time, it remains an important component of formal ENGOs, which represents an updated version of environmental reformism/conservationism. Additionally, radical anti-capitalist groups, often related to local agriculture and independent farms, have carried out their activities on a more political/cultural level (Bertuzzi, 2019a). Along with these different attitudes, new forms of activism are developing in Italy as well.…”
Section: Brief Historical Contextualisationmentioning
confidence: 99%